Enlightening the path of dentistry: Lasers - A brief review - Sudhanshu Srivastava; Sumit Kumar Misra; Devendra Chopra; Purnima Sharma (Wolters Kluwer Medknow Publications, 2018)
Lasers were brought into the field of clinical dentistry with the expectation of conquering a portion of the downsides postured by the customary strategies for dental practice. One of the primary objectives in dentistry is to give the treatment as agreeable as conceivable. The laser is being utilized as a part of various dental procedures including soft tissue surgeries, cavity preparation, caries removal, and caries detection. The utilization of current normal lasers in dentistry brought about less pressure and dread in patients amid dental techniques, likewise prompting more moderate nonobtrusive strategies for delicate and hard tissues with insignificant discomfort and bleeding. This article will briefly elaborate uses of laser in dentistry.